Explaining success of performance management systems : the role of chain of key factors - Laitinen, Erkki K.; Kadak, Tarmo (Emerald, 2019)
Purpose: The purpose of this paper is to use the logical chain of key factors (KFs) to explain the success of performance management systems (PMS) and corporate performance. Design/methodology/approach: The authors use the strength of the KFs chain to capture PMS success. First, the authors assume that perceived environmental uncertainty (PEU) is positively associated with the strength (H1). The higher the PEU, the stronger is the chain as a response to uncertainty. Second, the authors assume that the strength improves performance (H2) but third, that the impact of the strength is negatively moderated by competition (H3). Fourth, the authors assume that this improvement leads to superior corporate performance (H4). The research model is tested by applying the partial least squares method for a sample of 61 Estonian and Finnish firms. Findings: Empirical evidence shows that PEU is negatively correlated to the strength of the chain but when controlled for a set of control variables, the path coefficient is positive. The strength of the chain is positively associated with improvement in performance. The impact of the strength of the chain on financial performance is negatively moderated by competition. The improvement in performance is positively associated with the attainment level of strategic goals. The improvement in non-financial performance does not significantly affect corporate profitability. Practical implications: The levels of PEU and competition should be taken into the account when designing, adjusting and assessing the PMS of organization. Originality/value: The authors give explanation why evidence about the effects of PMS on the performance of the firm is mixed.
Keywords: chain of key factors (KFs); competition; performance; performances; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|